Bio‐inspired nanofunctionalisation of biomaterial surfaces: a review. Issue 3 (10th September 2019) - Xie, Chaoming
Abstract : The surfaces of biomaterials determine their efficacy and hence, have an important role in clinical applications. Through bio‐inspired surface nanofunctionalisation, the surface properties of biomaterials such as physical morphology and chemical composition can be tailored using biomimicry. It is a powerful tool for improving the interactions between the physiological environment and biomaterial surfaces. Therefore, research on bio‐inspired nanofunctionalised surfaces has attracted much attention in recent years. This review focus on the recent bio‐inspired strategies based on the structure of the extracellular matrix (ECM) and composition of mussel‐inspired polydopamine (PDA). The design, preparation, and properties of ECM and PDA‐inspired nanofunctionalised biomaterial surfaces are reviewed. I have also highlighted the effects of these bio‐inspired nanofunctionalised biomaterial surfaces on bone regeneration, cartilage repair, and antibacterial activities.